Predictors of Occupational Adaptation in Individuals With Parkinson’s Disease - Haj Ghani, Jafar; Taghizadeh, Ghorban; Azad, Akram; Habibi, Seyed Amir Hasan (Function and disability journal, 2025)
Importance: This assessment is essential for preserving independence, enhancing the quality of life, and promoting well-being through engagement in meaningful daily activities. Consequently, this study, which investigates predictive factors of occupational adaptation among individuals with PD, presents considerable relevance to healthcare professionals, researchers, and students in the field. Methodology: The study comprised 100 participants, with a mean age of 60.23 years (standard deviation = 9.27). Participants underwent a comprehensive evaluation using a battery of validated measures, including the Relative Mastery Scale, Hospital Anxiety and Depression Scale-Depression (HADS-D), Tilburg Frailty Indicator (TFI), Pittsburgh Sleep Quality Index (PSQI), Falls Efficacy Scale-International (FES-I), Fatigue Severity Scale (FSS), Parkinson Disease Questionnaire-39 (PDQ-39), and Lille Apathy Rating Scale (LARS). These instruments were selected to provide an in-depth assessment of the factors impacting occupational adaptation in PD. Results: The results derived from regression models indicated that quality of life, frailty, apathy, and sleep quality accounted for 18%, 22.5%, 27.1%, and 29.7% of the variance in occupational adaptation, respectively. Quality of life emerged as the predominant predictor of occupational adaptation across all stepwise models. Conclusion and Relevance: This study's findings have significant implications for assessing and managing occupational adaptation in individuals with Parkinson's disease. The study identifies quality of life, frailty, apathy, and sleep quality as critical predictors, with quality of life recognized as the most influential factor affecting occupational adaptation. This understanding not only empowers healthcare professionals, researchers, and students but also inspires them to formulate more effective interventions and strategies, thereby contributing to the advancement of the field.